The Effect Of Leverage, Liquidity, Inventory Turnover On Financial Distress With Profitability As An Intervening Variable (In Construction Sector Companies Listed on the Indonesia Stock Exchange for the Period 2017 - 2023) - Dodi Haryadi; Hari Gursida; Herdiyana Herdiyana (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the impact of Leverage, Liquidity, and Inventory turnover on Financial Distress with Profitability as an intervening variable in construction sector companies listed on the Indonesia Stock Exchange (IDX) during the period of 2017–2023. The research adopts a quantitative approach using regression analysis with EViews 13 and mediation testing using the Sobel Test. The results indicate that Leverage has a significant negative impact on Financial Distress, but does not mediate this relationship through Profitability. Meanwhile, Liquidity does not have a significant effect on Financial Distress, either directly or through Profitability. Inventory turnover has a significant positive effect on Profitability, but does not significantly affect Financial Distress, either directly or through Profitability as an intervening variable. On the other hand, Profitability was found to have a significant positive impact on Financial Distress, indicating that higher profitability increases the likelihood of experiencing financial distress. The mediation test results show that Profitability does not mediate the relationship between the independent variables (Leverage, Liquidity, and Inventory turnover) and Financial Distress significantly. These findings suggest that, although good financial management is important, in the construction sector, other factors such as project management and capital structure have a greater impact on a company's financial condition. This study provides practical implications for construction sector management in planning more cautious financial strategies and considering sector dynamics that can affect the stability of company finances in a more comprehensive way.